ANALISIS SEKTOR UNGGULAN DI KABUPATEN MINAHASA TENGGARA (Leading Sectors Analysis in Southeast Minahasa Regency) - Silvanaria Marce Arikalang; Olly Esry Laoh; Rine Kaunang (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2019)
The research aims to analyze the leading sectors in the Southeast Minahasa Regency and to analyze the contribution of the leading sectors in the Southeast Minahasa Regency. This study used a quantitative descriptive approach. The data used were secondary data in the form of Gross Regional Domestic Product of Southeast Minahasa Regency and Gross Regional Domestic Product of North Sulawesi Province in the period of 2013-2017, on the basis of Constant Price in 2010.Â Analysis of the data used in this study, namely quantitative descriptive analysis, including the contribution of economic sectors to the GRDP of Southeast Minahasa Regency, location quotient analysis and shift share analysis. The results of this study indicated the agriculture, forestry and fisheries sector, the mining and quarrying sector, the electricity and gas procurement sector, the construction sector, the transportation and warehousing sector, as well as the real estate sector in Southeast Minahasa Regency, had LQ scores above 1. The agriculture, forestry and fisheries was the sector with the largest contribution to the Southeast Minahasa Regency GRDP in the 2013-2017 period. The role of the leading sector through the calculation of regional shares (Nij) to the Province of North Sulawesi showed positive results. In the proportional shift (Mij) calculation only the agriculture, forestry and fisheries sectors got negative values. In the differential shift calculation (Cij), some sectors in Southeast Minahasa Regency received negative values or did not have competitiveness against similar categories at the provincial level. Those sectors were mining and quarrying, electricity and gas procurement, transportation and warehousing.Keywords: Leading Sector, Location Quotion, Shift Share, Southeast Minahasa Regency